Biofuels production by chlorella sorokiniana in a biorefinery perspective - Constantino, Ana (2020)
Biofuels Production By Chlorella Sorokiniana In A Biorefinery Perspective (Poster Presentation) in Abstract Book 5th Algaeurope Conference